Westdeutsche Fibel für Hilfsschulen - Ebbinghaus, Adolf; Vogt, Rudolf; Wenz-Viëtor, Else; Hoffmann, Heinrich (Verlag L. Schwann, 1939)
Kleine Druckschrift -- Große Druckschrift -- Lesestücke ohne Silbentrennung